The potential of organic waste as a substrate for anaerobic digestion in Ukraine: trend definitions and environmental safety of the practices - Chernysh, Yelizaveta; Vladimir, Shtepa; Roy, Igor; Chubur, Viktoriia; Skvortsova, Polina; Anastasia, Ivlieva; Danilov, Dmitry (Видавництво Львівської політехніки, 2021)
This article is devoted to the analysis and prospects of using different types of organic waste to achieve environmental goals. Due to the unique climate and natural resources, Ukraine has significant potential for biomass, the processing of which should solve urgent problems with the disposal of waste, as well as the production of alternative energy sources and biofertilizers. The preferred substrates for anaerobic digestion in Ukraine, considering the technological feasibility, availability, and volume are animal manure (cattle, pigs), bird droppings, plant residues, industrial sludge, common sludges. After analyzing the statistics for 2015-2019, the groups of dominant wastes were identified, and with the help of the built-in function “TREND”, the forecast of the waste potential with an organic component for 2021–2026 was constructed. Examining the obtained indicators for different types of waste, the reasons for the tendency of decrease or increase in their formation in the next five years were revealed. The direction of enhancing the sustainability of bioenergy, achieving environmental goals through the bioprocessing of organic waste associated with the ecological safety of production processes were discussed.
Keywords: organic wastes; anaerobic digestion; waste potential forecast; biofuels; biofertilizers; digestate